2013
DOI: 10.3998/mjs.12333712.0001.006
|View full text |Cite
|
Sign up to set email alerts
|

Are Green Cities Nice Places to Live? Examining the Link between Urban Sustainability and Quality of Life

Abstract: The growing importance of nonmarket assets such as the environment, combined with the unprecedented availability of high-resolution data, has renewed broad interest in quantifying sustainability at different spatial levels. Policy-related decision making requires that potential sustainability measures meet three key requirements: (i) sustainability metrics need to be comprehensive so that they reflect the experience of representative households, (ii) sustainability indices need to be comparable across differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Climate, environmental, and water crises affect the quality of life and well-being of residents in many ways, comprising one of the most urgent and important challenges facing modern cities. In the context of a broad debate on QoL assessment, sustainability, and livability indices [5,32,94], the socio-ecological paradigm emerges [83,88,94], which highlights the close links between QoL and climate and environmental variability [3,[31][32][33]. Moreover, the aging of societies poses new challenges for the assessment of factors determining the quality of life in cities [4,36,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate, environmental, and water crises affect the quality of life and well-being of residents in many ways, comprising one of the most urgent and important challenges facing modern cities. In the context of a broad debate on QoL assessment, sustainability, and livability indices [5,32,94], the socio-ecological paradigm emerges [83,88,94], which highlights the close links between QoL and climate and environmental variability [3,[31][32][33]. Moreover, the aging of societies poses new challenges for the assessment of factors determining the quality of life in cities [4,36,46].…”
Section: Discussionmentioning
confidence: 99%
“…This is a serious cause for concern. Given the SDGs [2] and urban development agendas (e.g., ICOMOS_SDGs_Policy_Guidance_2021 [86], European New Bauhaus [87]), the significance and construction of global city rankings definitely necessitate a recalibration of the basics [88].…”
Section: Comparison Of the Winning Cities In Qol And Sandr Rankingsmentioning
confidence: 99%
“…The recent rapid and intense urbanization has often resulted in an over consumption of water, energy, raw materials, land, and production of waste and air pollution. Poor environmental quality and ecological efficiency, together with a scarce infrastructure development and traffic congestion, negatively affect the economic competitiveness, livability, and attractiveness of cities [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research has shown slight correlations between broad measures of SD (which usually include a measure of population density), and indices of human well-being. For example, researchers have attempted to connect happiness in U.S. cities to the presence of sustainable urban development policies and amenities such as utilities, resources, and the built environment (Bieri, 2013;Cloutier, Jambeck, & Scott, 2014;Cloutier, Larson, & Jambeck, 2014). looked at the MSA-level using four established indices of urban sustainability: The Green City Index, Our Green Cities, Popular Science's U.S.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The increased practice of sustainable development has been shown to be related to improvements in many aspects of civic well-being (Bieri, 2013). However, the nature of this relationship is broad and vague.…”
Section: Quality Of Lifementioning
confidence: 99%